Strategi Guru dalam Upaya Meningkatkan Minat Baca dengan Media Video di Kelas 3 MI NU Matholiul Falah dalam Pembelajaran Bahasa Indonesia - Hanik, Elya Umi; Arumdiyah, Ita Amalia; Hilmiyah, Akif; Wijayanti, Dhivani Artha (Lembaga Yasin AlSys, 2022)
This article contains strategies to increase reading interest in third grade students of MI NU Matholiul Falah and teachers' strategies in the learning process in 2021/2022. This type of research is a qualitative research with a descriptive approach. This study aims to increase students' reading interest by using video media and singing methods. This classroom action research was carried out in 1 cycle with four stages, namely: planning, implementation, observation, reflection. The object of this research is the third grade students of MI NU Matholiul Falah in the Japanese village, Mejobo, Kudus, totaling 29 students. The research instruments used were observation sheets, interview guidelines, questionnaire sheets, and documentation. The results of the analysis based on observations, interviews, and questionnaires can be obtained that the reading interest of the third grade students of MI NU Matholiul Falah is low. Factors that influence this are the existence of internal and external factors. The results showed that the use of video media and singing methods in Indonesian language learning materials could increase students' reading interest which was marked by an increase in completeness in 1 cycle (87%) with an average value of 89,85.